1981
DOI: 10.1080/00220671.1981.10885315
|View full text |Cite
|
Sign up to set email alerts
|

Causal Perception of Pupils’ Success or Failure by Teachers and Pupils: A Comparison

Abstract: This study compared causal perceptions of teachers and pupils regarding pupils' success or failure on a test. Specifically, following a test in a classroom, pupils were asked to evaluate their grade as a success or failure and to attribute causality to the outcome. At the same time, the teacher was asked to fill out the same questionnaire concerning each pupil in the class. This procedure was repeated in eight classrooms. Teachers were found to attribute success to themselves, to home conditions, and to effort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…This finding suggests that teachers perceive students as solely responsible for their poor grades. Further, Darom and Bar-Tal (1981) revealed that teachers anticipate academic improvement when they see a change in a student's behavior and that academic improvement is not a function of changes in teacher behavior. Darom and Bar-Tal (1981) also found that elementary students shared teachers' perceptions of who was responsible for success and failure situations.…”
Section: Academic Outcomesmentioning
confidence: 95%
See 2 more Smart Citations
“…This finding suggests that teachers perceive students as solely responsible for their poor grades. Further, Darom and Bar-Tal (1981) revealed that teachers anticipate academic improvement when they see a change in a student's behavior and that academic improvement is not a function of changes in teacher behavior. Darom and Bar-Tal (1981) also found that elementary students shared teachers' perceptions of who was responsible for success and failure situations.…”
Section: Academic Outcomesmentioning
confidence: 95%
“…Further, Darom and Bar-Tal (1981) revealed that teachers anticipate academic improvement when they see a change in a student's behavior and that academic improvement is not a function of changes in teacher behavior. Darom and Bar-Tal (1981) also found that elementary students shared teachers' perceptions of who was responsible for success and failure situations. Further, elementary students perceived academic failure as a result of their own internal weakness, specifically, their lack of ability.…”
Section: Academic Outcomesmentioning
confidence: 95%
See 1 more Smart Citation
“…But there is evidence (Darom & Bar-Ial, 1981) that teachers accept their responsibility for success but not for failure. Lastly, Weiner's first explanation (lack of effort is socially undesirable) may not be sufficient in that lack of ability is equally (or more) socially undesirable (see the example of intelligence in Mugny, 1985).…”
Section: Teachers' Explanations Of Academic Success and Failurementioning
confidence: 99%
“…This behavior impacts on teachers by reinforcing preconceived ideas that children who are successful in school come from stable, less alienated backgrounds (Darom & Bar-tal, 1981). The child's success is related to the family's ability to socialize their children and inculcate positive attitudes toward school (Fuller, 1984).…”
mentioning
confidence: 99%